Metacognitive Self and Motivation to Seek Diagnostic Information About the Self: A Longitudinal Study - Brycz, Hanna; Kleka, Paweł; Fanslau, Agnieszka; Pilarska, Aleksandra (Frontiers in Education, 2019)
AbstractThis longitudinal study was designed to test the hypothesis that the strength of metacognitive self would predict the level of motivation to obtain self-diagnostic information. We begin by defining the construct of metacognitive self as a cognitive-motivational concept that pertains to the individuals’ self-awareness of biases. We then discuss the role of acquiring diagnostic information about the self in enhancing self-regulation. We predicted that stronger metacognitive self would be associated with greater motivation for seeking diagnostic information about the self, including both positive and negative feedback. More than 400 undergraduate university students participated in the 2.5-year longitudinal study. Participants were tested 5 times, with 6-month intervals, using measures of metacognitive self (Metacognitive Self Questionnaire; MCSQ-21) and the need for diagnostic information about the self (Self-Diagnostic Motive Scale; SDMS). As expected, participants with high metacognitive self sought diagnostic information about themselves significantly more than those low in metacognitive self. This effect was observed at each of the five measurement points. We conclude that individuals characterized by greater insight into their own biases are more highly motivated to obtain feedback about themselves that can be used for